Glucose disturbances in non-diabetic patients receiving acute treatment with methylprednisolone pulses - Tamez Pérez, Héctor Eloy; Gómez de Ossio, María Dolores; Quintanilla Flores, Dania Lizet; Hernández Coria, Mayra Ivonne; Tamez Peña, Alejandra Lorena; Cuz Pérez, Gissén Jazmín; Proskauer Peña, Stephanie Lissette (2012)
Objective: Methylprednisolone pulses are used in a variety of disease conditions, both for acute and chronic therapy. Although well tolerated, they increase glucose levels in both non-diabetic and diabetic patients. They may also be considered a significant risk for acute metabolic alterations. The purpose of this report is to determine the metabolic changes in blood glucose levels in non-diabetic patients receiving methylprednisolone pulses and identify the presence of predictive factors for its development. Methods: Observational, prospective study in 50 non-diabetic patients receiving 1 g intravenous methylprednisolone pulses for three consecutive days as an indication for diverse autoimmune disorders. Demographic, anthropometric, and metabolic variables were analyzed, and glucose, insulin and C-peptide levels after each steroid pulse were identified. Different variables and the magnitude of hyperglycemia were analyzed using Pearson’s correlation. Results: 50 patients were included, predominantly women (66%, n = 33). The average age was 41 ± 14 years with a BMI of 26 ± 3 kg/m2 . Baseline glucose was 83 ± 10 mg/dL. After each steroid pulse, glucose increased to 140 ± 28, 160 ± 38 and 183 ± 44, respectively (p <0.001). C-peptide and insulin concentrations increased significantly (p <0.001). The prevalence of fasting hyperglycemia after each pulse was 68%, 94% and 98%, respectively. We found no correlation between the magnitude of hyperglycemia and the studied variables. Conclusion: Methylprednisolone pulses produced significant increases in fasting glucose in most patients without diabetes. Further studies are needed to define its role in long-term consequences.